A case of midgut malrotation presenting as subacute intestinal obstruction in an adult - Mathangasinghe, Yasith; Samaranayake, U.M.J.E. (The College of Surgeons of Sri Lanka., 2018)
Midgut malrotation occurs due to variations of rotation and fixation of the intestine during fetal development. Over 90% of cases present during the neonatal period [1]. The reported incidence of adult midgut malrotation is between 0.0001% and 0.2% [1, 2]. Adults with intestinal malrotation present with atypical symptoms [1] requiring a high degree of clinical suspicion in diagnosis.
Keywords: Malrotation; ladd band; intestinal obstruction